Assessing stakeholder's experience and sensitivity on key issues for the economic growth of organic aquaculture production. (January 2018) - Lembo, Giuseppe; Jokumsen, Alfred; Spedicato, Maria Teresa; Facchini, Maria Teresa; Bitetto, Isabella
Abstract: Participatory management is widely recognised as a working method of paramount importance, based on the principles of knowledge sharing, accountability and legitimacy. Hence, it is broadly considered suitable for addressing issues related to the sustainable development of the seafood industry, and specifically, of the aquaculture system. A survey focused on the current EU regulatory framework was carried out to elicit stakeholders' preferences, knowledge and experience on key issues for the development of organic aquaculture, supported by science-based regulations. The survey was completed by 65 stakeholders belonging to several categories, and it was supported by the implementation of the Analytic Hierarchy Process method. Stakeholders' preferences were elicited on organic production methods and control systems, the quality of the environment and organic products, fish health and welfare. The views expressed by the participants revealed both competence and awareness, despite the complexity of the subject. Several ideas and useful suggestions emerged regarding unresolved technical issues. In addition, the need for a targeted communication strategy on the quality of organic aquaculture products and the necessity of fostering European/national programs to support the production and marketing of organic aquaculture products were highlighted. Highlights: Organic principles does rely on a holistic concept of sustainability. Consumers' opinion is a key factor for boosting organic production. Integrated Multi-Trophic Aquaculture is perceived in line with organic principles. Recirculation Aquaculture Systems are not perceived in line with organic principles. A communication strategy on the qualities of organic aquaculture would be advisable.